Draft Genome Sequence of Salmonella enterica Serovar Typhi Strain STH2370 - Valenzuela, Camila (American Society for Microbiology, 2014)
We report the draft genome sequence of Salmonella enterica serovar Typhi strain STH2370, isolated from a typhoid fever patient in Santiago, Chile. This clinical isolate has been used as the reference wild-type strain in numerous studies conducted in our laboratories during the last 15 years.